PENGARUH ISLAMIC SOCIAL REPORTING (ISR), UMUR PERUSAHAAN DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP PROFITABILITAS (ROA) PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2010-2014 - Nurlaila Harahap; Hendra Harmain; Saparuddin Siregar; Nova Maharani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
This research is aimed to observe and analyse factors which influence Profitability (ROA) in companies which are administered in the Jakarta Islamic Index (JII) from 2010 to 2014. The factors which are tested in this research are the Islamic Social Reporting (ISR), Company’s age and the public shareholding as the independent variable, and Profitability (ROA) as the depedent variable. The sample of this consist of twenty companies, which are listed in the Jakarta Islamic Index (JII) and have sent their financial reports to Bapepam in the period of 2010-2014. The data used in this research is the secondary data and the sampling technique used is the purposive sampling method. The data analysis used is the multiple linear regression analysis. This research used F-test to find out simultaneous influences among ISR, company’s age and public shareholding on ROA. This research also used T-test to test partial correlation of each independent variable to the dependent variable. According to the analysis results of T-test, it shows that all variables have sifnificant influences on Profitability (ROA).